A passion for juice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Around 1,000 farmers and labourers in Rwanda have now a stable income, thanks to the Aprojofugi farmers organisation spotting the potential of passion fruit (Passiflora edulis). Their market survey and business plan showed a firm proposition, and...